DIGITAL MODELING OF WHEAT AND SOYBEAN PRODUCTION BASED ON ECONOMIC AND MATHEMATICAL METHODS - Vladimirovna Berdnova, Ekaterina; Lazhauninkas, Julia Vladimirovna (Nauka Krasnoi͡a︡rʹi͡a, 2019)
In modern conditions of import substitution, the question of domestic production of crop products, including soybeans, is acute. Of course, soybeans is grown in Russia, but there are no suitable tools to optimize its production. There is an increasing need to obtain the greatest profit from the sale of soybeans, but there is no competent planning of acreage for various crops, including soybeans. We have constructed an economic and mathematical model of the distribution of acreage in the cultivation of wheat and soybeans, carried out the calculation using the simplex method, as well as the analysis of profit in their production. As a result of calculation we receive that on the identical sown area profit from cultivation of wheat makes 152691 RUB, profit from cultivation of soybeans – 19405510 RUB. We propose to implement in existing digital platforms such a calculation to optimize the distribution of acreage by introducing economic and mathematical modeling on Purpose. Methods of economic and mathematical modeling to determine the optimal distribution of acreage in the production of soybeans in order to obtain the greatest profit, to analyze the profit from the sale of soybeans and wheat. Methodology in article economic-mathematical methods based on the simplex method. Results: the most informative parameters reflecting the optimal distribution of acreage for soybean cultivation are received. Practical implications it is expedient to apply the received results advisable to implement in existing digital platforms to optimize the distribution of acreage by introducing economic and mathematical modeling based on the simplex method.